O imaginário midiático sobre os imigrantes indígenas venezuelanos: ¿um problema de humanidade? - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
This work presents a study on Social Imaginaries, and analyzes how the media from its information production contributes to the construction and reconstruction of them, be-ing of relevance within journalistic matters each element that conforms thus the idea that wants to be passed on to a sector of society, specifically in the population of Manaus through the news published in the print and digital newspapers, A Crítica and D24am on the arrival of the indigenous immigrants in Manaus. The study had a descriptive character, with a qualitative approach with a temporal cut from the month of February to August of the year 2017. Twenty subjects were analyzed in their visual structure, verify-ing in their titles, content and image the media visibility of the indigenous Venezuelan ethnicities It was verified that only in one of the twenty titles of the subjects was men-tioned the Warao ethnicity and still being mentioned within the contents of the subjects, the information presented around them was very scarce and infrequent, thus limiting the possibility of giving them the to know the population in a somewhat broader and more empathic way, leaving them in a distant place without a deeper understanding of their culture and identity. It was noticed three moments where the meanings of the perma-nence of the Waraos Indians in Manaus have changed since leaving Venezuela and ar-riving in Manaus, their strategies of survival and then as an expression of the social ques-tion with impact on municipal, regional and national government. It was verified the contribution of the image in the transmission of a message that not only passed infor-mation but that it helped to the compression of the subjects of the news, contributing a knowledge about them from the photographs that portray part of its culture besides its physiognomy and gestural characteristics, of behavior and clothing of the Venezuelan indigenous Warao ethnic group. From the titles and the content of the materials there was a tendency to the homogenization of the emigrants of Venezuela in Manaus without highlighting the differences of race and culture. The receiving community of Manaus manipulated through the press superfluous information, some of them biased, which highlight the negative more than the qualities that could bring benefits to the coexist-ence of both cultures.
Keywords: .; CIENCIAS SOCIAIS APLICADAS: SERVICO SOCIAL; Imaginários sociais; Migração venezuelana; Indígenas da etnia Warao; Meios de comunicação